(untitled) (AmeriQuests, 2019)
Since their origins in the post-World War II decades, American suburban communities have been battlegrounds for racial and socioeconomic conflict. Serving as enclaves for White privilege, many were purposefully designed to keep working class and minority residents out. Willow Lung-Amam’s Trespassers? Asian-Americans and the Battle for Suburbia examines the bitter social and cultural tension that has plagued the affluent Silicon Valley suburbs since an influx of Asian-American immigrants in the 1970s. Her narrative illustrates how, by their very nature, suburban communities regress toward homogenity, enforcing ideas of who is welcome through their physical landscapes. However, it also inadvertently suggests that if we can use community planning, town ordinances, and other tools and practices to deliberately exclude, we too can use them to include. As our country continues to diversify, but also stratify, it is important that we create suburban landscapes that foster diversity, welcome newcomers, give everyone a shot at achieving their version of the American dream.